Gender Differences in the Association Between Obesity Indices and Chronic Kidney Disease Among Middle-Aged and Elderly Taiwanese Population: A Community-Based Cross-Sectional Study - Chen, I-Ju; Hsu, Le-Tien; Lu, Mei-Chun; Chen, Ying-Jen; Tsou, Meng-Ting; Chen, Jau-Yuan (Frontiers in Endocrinology, 2021)
We aimed to investigate which of the three obesity indices has the strongest association with CKD and to explore whether there are gender differences in these relationships in the middle-aged and elderly Taiwanese population. This was a cross-sectional, community-based study. It included 400 residents (age 50–90 years) residing in a community in northern Taiwan. Each participant was asked to fill a questionnaire that collected personal information, medical history, medication use, and anthropometric measurements. The laboratory data were obtained by testing the blood and urine samples. The baseline characteristics were compared, and the obesity indices included body mass index (BMI), waist circumference (WC), and visceral adiposity index (VAI). CKD was defined as the presence of renal dysfunction (urine albumin-creatinine ratio ≥30 mg/g) or estimated glomerular filtration <60 mL/min/1.73m2. We used a multiple logistic regression model to evaluate the association between each obesity index and CKD for both genders. Further, we used the area under the receiver operating characteristic (ROC) curve (AUC) to examine the best obesity indices to predict CKD in different genders. The average age of the subjects was 64.47 ± 8.45 years, and men were significantly older. CKD was found in 31 (22.0%) males and 50 (19.3%) females. In men, there was no significant difference between the CKD and non-CKD groups among the three obesity indices. However, in women, only VAI was significantly higher in subjects with CKD (1.9 [1.1, 3.4]) than in subjects without CKD (1.5 [1.0, 2.2]) (p-value = 0.03). The multivariate logistic regression revealed that even after adjusting for possible confounding factors, VAI was found to be an independent risk factor for CKD in women (OR: 1.32, 95% CI: 1.04-1.69, p = 0.02), but not in men (OR: 1.20, 95% CI: 0.85-1.69, p = 0.30). The AUC of VAI had a significant ability to predict CKD in women but not in men. Our results showed that among the three obesity indices, VAI had the strongest association with CKD compared to BMI and WC only in women.